A single-layer micromachined tunable capacitor with an electrically floating plate. (14th March 2016) - Khan, Fahimullah; Zhu, Yong; Lu, Junwei; Pal, Jitendra; Dao, Dzung Viet
Abstract: This paper reports a novel micromachined tunable capacitor with an electrically floating movable plate. The device has been fabricated from a single metal layer based on a low-cost standard process. Tunable capacitors with electrically floating and non-floating plates have been characterized and compared with each other by using the same fabricated device with different configurations. The floating tunable capacitor exhibits a higher quality factor ( Q -factor) compared to a non-floating capacitor by eliminating the spring's resistance loss in radio frequency signal path. The device is actuated by an electro-thermal actuator to achieve high capacitance tuning range without the pull-in effect issue of parallel-plate electrostatic actuators. Experimental results show that the tunable capacitor has a wide capacitance tuning range of 631% with a low actuation voltage of 0.72 V. The floating tunable capacitor has a Q -factor at 1 GHz of 24.4, which is 5.5 times higher than that of a non-floating traditional tunable capacitor fabricated on the same chip.